Метали в системі “технозем – Robinia pseudoacacia L.” у рекультиваційних насадженнях Степу України - Зверковський, В. М.; Zvierkowsky, V.; Ситник, Світлана Анатоліївна; Sytnyk, Svitlana (Дніпровський державний аграрно-економічний університет, 2017)
Досліджено вміст неорганічних контамінантів-металів (Sb, Pb, Cd, As, Ni, Cr) у деревині й корі стовбура, листках та плодах Robinia pseudoacacia L., що становить рекультиваційне насадження на техноземі вугільних шахтних відвалів. Отримані дані хімічних речовин субстрату вирощування робінії перевищують значення ГДК. Максимальні концентрації майже всіх досліджуваних металів зафіксовано у фракції листки, вищого концентрування досягав Нікель. Згідно зі значеннями коефіцієнтів біоакумуляції, усі досліджувані метали належать до елементів слабкого накопичення, Арсеніум та Нікель депонуються в надземній фітомасі дерев робінії найменше. Raising of problem. Find toxicants resistant wood species and their deposits properties is important tasks of environment research. Wood and bark tissues can to retrieve inorganic contaminants from environment and to accumulate on longer time. Over the past decade, studies the experimental confirmation prospects of phytoremediation method for optimize the transformed landscapes.The aim of the research establishment of laws deposits properties of inorganic contaminants in different fractions of the aboveground biomass plants black locust and its reclamation potential in the mine sites.Materials and research methods. The plots was put down in the site of the forest restoration mine enterprise “Pavlogradskaya” in Pavlograd sity Dnipropetrovsk region. The object of the study served the a fractions in the black locust aboveground biomass (wood trunk, wood bark, leaves, fruit) aged 41 years, which growing at tehnozem substratum in the reclamation plantings.Determined the concentration of the metals (Sb, Pb, Cd, As, Ni, Cr) in the black locust wood trunk, bark trunk, leaves and fruit from restoration stands which growing on the tehnozem substratum determinate the method of the plasma-optical emission spectrometry (ICP– OES).Research results. Discussion. Indicators metal content in the test tissues in the varying degrees exceeded limit values chemicals in soil: Pb – 1,3; Cd –5,3; Ni – 10,8; As – 12,9; Cr – 15,7, except Stybium concentration which was a range of normal values. Note that set the concentrations do not exceed the limits of what is phytotoxic.Inorganic contaminants on the acid substrates, which is the study tehnozem (pH 4,6–4,8) have different degrees of the mobility, Plant tissues of the aboveground phytomass capable of varying intensity metals accumulate, so the next stage of the research definition of the metal concentrations in the compartments black locust aboveground biomass.In absolute values of the content of these substances belong to the group of inorganic contaminants low concentrations. The range of values in the fractions of black locust aboveground biomass is 0,8–9,5 mg/kg absolutely dry matter.Equal concentration in all investigated aboveground biomass compartments – 4,4–4,6 mg/kg showed Lead. Chrome had the same concentration – 1,7 mg/kg in all fractions, except the leaves, where it was more intense concentration – 2,8 mg/kg. The distribution Stybium found equal representation in the trunk wood and trunk bark tissues (0,8 mg/kg) and its dual exceeding the said concentrations in the leaves and fruits.Іn a fraction of aboveground biomass of leaves fixed maximum concentration for almost all metals studied, from which the largest concentration of Nickel – 5,5 mg/kg of absolutely dry matter. Trunk wood and trunk bark has a smaller concentration than in the leaves and have individual characteristics according to each metal. In fractions of wood trank more concentration relative to the brank trunk fixed for Nickel, Cadmium, Arsenium 4,8; 4,7 and 3,5 respectively. Same content per unit mass of absolutely dry matter discovered for Lead, Chromium and Stybium.Conclusion. Black locust fruits maximum concentration became Nickel – 8,5 mg/kg, it is the maximum concentration detected for the studied inorganic contaminants in all fractions of the aboveground biomass of Robinia model trees in restoration stends. The lowest content of the black locust fruits Chromium and Arsenium showed. According with literature data translocation coefficient of the metals from soil to plant are: Pb and Cr – 0,01–0,1; Ni and Cu – 0,1–1,0; Zn and Cd – 1,0–10,0. The calculated values of the translocation coefficients, which demonstration biological accumulation by Robinia aboveground biomass compartments are consistent with literature data.According to the obtained bioaccumulation coefficients all studied metals in the system “black locust–tehnozem” belong to the elements of weakly accumulation. Most value of translocation coefficients was recorded for Cadmium in the fraction leaves. Such substances as Arsenium and Nickel deposited in black locust aboveground phytomass least.
Metals in the system “technozen – Black locust” in the restoration stands within steppe zone in Ukraine
Keywords: надземна фітомаса; aboveground biomass; робінія несправжньоакація; black locust; неорганічні контамінанти-метаи; inorganic contaminants; рекультивація; forest restoration